Clarification of guava juice through membrane-based process - Mohd Omar, Jusrianti; Mohd Nor, Mohd Zuhair (Malaysian Society of Agricultural Engineers, 2019)
This study was aimed to explore the potential of using membrane-based process for the clarification of fresh guava juice. The study was done to determine the effect of the process on the permeate flux behavior as well as the guava juice quality attributes such as pH, turbidity and total soluble solids (TSS). The clarification of guava juice was performed using 100 kDa polymeric membrane in a dead-end module. The clarification process exhibited high productivities in terms of permeate flux (12.72 -60.94kg/m²/hr) at a processing pressure of 1 bar. The process has also resulted a high reduction of turbidity (95%) in the permeate with 5.67% reduction of TSS. No significant change was observed in terms of the pH of the feed, permeate and retentate. The findings indicate that ultrafiltration can be successfully used in guava juice clarification.